From the strange death to the odd afterlife of Lutheran England - Gehring, David S. (Cambridge University press, 2014)
Research on the relationship between England and Protestant Germany during the sixteenth century has recently experienced a revival. A significant area of concentration for confessional interests among Lutherans a century ago, Anglo-German relations took a backseat in Reformation historiography during the twentieth century, but during the last decade or so a host of scholars in the UK, Germany, and USA have once again turned their attention to the topic. This review article surveys trends in scholarship on Reformation studies in both England and Germany before turning specifically to works considering instances of interaction, co-operation, and adaptation across the confessional and geographic divides. Gathering a considerable array of secondary materials, the article offers an overview of the merits and criticisms of previous analyses and concludes by pointing out a few areas for future inquiry.